Answer:
a) y = 6x - 3
b) 1/3y = 2x -1
The first thing you need to do is isolate (y) in the second equation
3 x (1/3y) = 3 x (2x - 1)
y =6x - 3
After isolating (y) in equation b they end up being the same.
Graphing:
In order to graph this, you have to make the first point at (0, -3) since this is the Y-intercept of the equation.
In order to graph the other points, you must move 6 units up and 1 unit to the right. Or vise versa If you need a visual I'll gladly link one.
Answer:
The correct option is;
(3) The sample of track athletes show that there is a correlation between foot size and running speed
Step-by-step explanation:
The statements are analysed as follows;
(1) Smaller foot sizes cause track athletes to run slower.
The above statement is a conclusion and it infers more information than is contained in the question statement because there are other factors such as taller athletes run faster than average sized athletes
(2) The sample of track athletes shows a causal relationship between
foot size and running speed.
The above statement is similar to the one above as it is a milder conclusion and it infers more information than is contained in the question statement
(3) The sample of track athletes shows a correlation between foot size
and running speed.
The above statement is correct as is directly supported by the data as it is a statement made based directly the data
(4) There is no correlation between foot size and running speed in
track athletes.
The above statement is not supported by the available data.
2:7 = 4:14 because each is equal to 2/7. If you simplify 4:14 by dividing by 2, it simplifies to 2:7.
Answer:
I think the answer is b
Step-by-step explanation:
3cos(x)+3
Answer:
3
Step-by-step explanation:
The value of "a" is the coefficient of x^2, so we know that is 2.
__
<u>Solve for h</u>
Now, we have ...
2x^2 -8x +7 = 2(x -h)^2 +k
Expanding the right side gives us ...
= 2(x^2 -2hx +h^2) +k
= 2x^2 -4hx +2h^2 +k
Comparing x-terms, we see ...
-4hx = -8x
h = (-8x)/(-4x) = 2
__
<u>Solve for k</u>
Now, we're left with ...
2h^2 +k = 7 = 2(2^2) +k = 8 +k
Subtracting 8 we find k to be ...
k = 7 -8 = -1
__
And the sum of constants a, h, and k is ...
a +h +k = 2 +2 -1 = 3
The sum of the constants is 3.